Politicization of Football and International Relations in Europe (Case Study: Stances of Football Institutions in Europe in the Conflict of Russia-Ukraine) - Kristianto, Yohanes Ivan Adi; Fachrie, Muhammad; Widanti, Eki Melina; Atmojo, Wijoseno Cahyo (WIMAYA, 2024)
Football, one of the most popular sports in the world, has never been separated from political aspects. In Europe, at least since the World War, football has been used by governments as a propaganda tool. At other times, football is the first to initiate entry into the world of politics, such as UEFA's decision to involve football clubs and the national team of Turkey in competing with European football clubs and national teams. Recently, the security conflict between Russia and Ukraine has given rise to political support by several football confederations in Europe. This research aims to identify the chain of politicization that occurs between the Russia-Ukraine conflict and the political attitudes of football confederations in Europe, using issue linkage theory. Next, this research, using European solidarity theory at the macro level, analyzes the implications of this chain of politicization for European integration. The research method applied in this research is basic research using secondary data. This research finds that on the issue of the Russia-Ukraine security conflict, this issue controls the dynamics of football politics in Europe. Meanwhile, European solidarity occurs at the institutional level with a political orientation.